Stability of biological membranes upon mechanical indentation - Franz, Florian; Aponte-Santamaria, Camilo; Gräter, Frauke (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2018)
Mechanical perturbations are ubiquitous in living cells, and many biological functions are dependent on the mechanical response of lipid membranes. Recent force-spectroscopy studies have captured the stepwise fracture of stacks of bilayers, avoiding substrate effects. However, the effect of stacking bilayers, as well as the exact molecular mechanism of the fracture process, is unknown. Here, we use atomistic and coarse-grained force-clamp molecular dynamics simulation to assess the effects of mechanical indentation on stacked and single bilayers. Our simulations show that the rupture process obeys the laws of force-activated barrier crossing, and stacking multiple membranes stabilizes them. The rupture times follow a log-normal distribution which allows the interpretation of membrane rupture as a pore-growth process. Indenter hydrophobicity determines the type of pore formation, the preferred dwelling region, and the resistance of the bilayer against rupture. Our results provide a better understanding of the nanomechanics underlying the plastic rupture of lipid membranes.
Gesehen am 27.03.2019